AIMMS - Implementation of selected optimization problems - Kraváková, Marie; Jablonský, Josef, 1955-; Černý, Michal; Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky (2021)
The objective of this thesis is to build a simple application for solving optimization problems aimed primarily at business users. This application is created using the software AIMMS, specifically its prescriptive analytics platform. The optimization problems chosen for demonstrating the functionality of AIMMS are the distribution problems, respectively the transportation problem, the container transportation problem, and the allocation problem. A reader is guided through the whole process, from understanding the business context, transforming the business problem into a mathematical model, converting the model into the mathematical modelling language of AIMMS, linking the data and procedures to a user-friendly Web-based interface to lastly, being presented the end-user application. The thesis also includes information about the company behind the analytical product, the AIMMS community.
Vedoucí práce: Josef Jablonský
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby
Způsob přístupu: Internet
Keywords: matematické metody v ekonomii [obor bakal. práce]; bakalářské práce; bachelor's theses